15 Cardiac arrest survival versus defibrillation delay during ongoing CPR. (26th April 2019) - Franěk, O; Pekara, J
Abstract : Background: In case of cardiac arrest with ventricular fibrillation (VF CA), several studies confirmed decrease of survival chance by 10% per minute when resuscitation is NOT performed. On the other side, only a rare data are available to evaluate the influence of defibrillation delay when resuscitation IS performed until defibrillation is available. Method: This is a retrospective analysis of VF CA from Prague Utstein-style registry data from 2003 to 2018. We compared the outcome of patients where the collapse due to ventricular fibrillation onset was directly witnessed by EMS crew so that the defibrillation was available immediately (EMS-WITNESSED group) with outcome of patients who collapsed before emergency call, layperson CPR (without AED) was provided and the patients were found with VF CA by responding EMS crew (LAYPERSON-WITNESSED group). Results: In EMS-WITNESSED group there were 325 patients and 151 survivors (CPC 1–2), while in LAYPERSON-WITNESSED group there were 1741 patients and 679 survivors. That gives survival rates 46.5% and 39.0% respectively; RR=0.88. The average EMS response time (call-to-patient) was 8:48 min. Conclusion: If layperson CPR is performed from collapse to EMS arrival, the chance of survival from VF CA with defibrillation after almost 9 min after collapse reached as much as 88% as compared to the ideal situation where immediate defibrillation is available. Thus, maximal effort including dispatcher-assisted CPR should be focused to support layperson CPR. More studies are needed to clearly evaluate the real life benefit of AED programs in municipal setting. Conflict of interest: None. Funding: None.